In-between Bragg reflections: thermal diffuse scattering and vibrational spectroscopy with x-rays. (1st December 2015) - Bosak, A; Chernyshov, D; Wehinger, B; Winkler, B; Le Tacon, M; Krisch, M
Abstract: In the last decade diffuse scattering studies re-gained their place in the domain of lattice dynamics studies. The use of thermal diffuse scattering becomes particularly efficient when coupled with vibrational spectroscopy, where inelastic x-ray scattering can be advantageous compared to inelastic neutron scattering, and state-of-the-art ab initio calculations. We present a brief summary of the experimental and theoretical background, give an overview of the principal experimental implementations, and discuss a representative set of examples of such a combined approach.